STRATEGI PENGELOLAAN JALAN KOLEKTOR BERDASARKAN KONDISI FUNGSIONAL JALAN - Maria S.M. Nabu; Don Gaspar N. da Costa; Oktovianus E. Semiun (Program Studi Teknik Sipil Universitas Katolik Widya Mandira, 2023)
Road damage in general is a condition of road buildings that do not function both from a technical point of view, benefits, and safety. Road damage is one of the factors causing traffic jams and accidents. This study aims to determine the pattern of road handling based on the functional condition of the road on the Kupang urban collector road. The identification of the damage conditions is carried out using the SDI formula wherein the damage conditions are determined by the level of road damage on each of the observed roads. Furthermore, based on the level of road damage, a road handling strategy is determined. In this case, because the quality of accessibility and mobility services between regions is affected by not only physical connectivity but also functional aspects, to facilitate the process of identifying the service performance of the collector road network, a road functional condition mapping model is used. The results of the mapping clearly show which segments and/or parts of the road are damaged and have an impact on the smoothness and safety of inter-regional travel. That's why QGIS is used for the mapping. The results showed that in the Maulafa sub-district, out of a total of 17 sections in the region, there were 6 roads that had to be repaired. The implication of the results of this study is that the results of the mapping of the functional condition of the road not only allow openness and at the same time ease of access, but also facilitate the preparation of programs for handling road damage and the provision of a budget for its management. Therefore, in the future this model needs to be developed through the use of WebGIS-based applications and by involving community participation in the aspect of supplying road condition data.